Pengaruh Label Halal dan Konformitas terhadap Keputusan Pembelian Produk McDonald’s yang Terafiliasi Israel pada Mahasiswa di Surabaya - Yasmin, Putri Alia; Susilowati, Fitriah Dwi (Jurnal Ekonomika dan Bisnis Islam, 2025)
Indonesia, as a country with a Muslim-majority population, places the halal label as an important factor in purchasing decisions. However, there is a gap between halal awareness and the actual consumption behavior of students amid the issue of boycotting products affiliated with Israel. The aim of this research is to analyze the influence of halal labeling and conformity on purchasing decisions for McDonald’s products affiliated with Israel among students in Surabaya. This research method uses quantitative methods with data sources using questionnaires distributed online. Sampling using purposive sampling technique with 100 respondents. The technique used in data analysis is multiple linear regression in SPSS 30 software. In this research, the results showed that there was an influence between halal labeling and conformity on the decision to purchase Israeli-affiliated McDonald’s products among students in Surabaya. This shows that students studying in Surabaya in consuming McDonald’s products still consider halal labeling in accordance with their responsibilities as Muslims who are openly ordered by Allah, as well as the influence of social groups to decide on purchases in adjusting consumption behavior through product preferences to be consumed